KETERLIBATAN KIAI DALAM POLITIK PRAKTIS DAN IMPLIKASINYA TERHADAP MASYARAKAT - Eko Setiawan (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2014)
Post-reformation many kiai plunge into the world of practicalpolitics. The scholars who had been consistently protect the publicand a representative of the people's hearts too busy to get into theworld of practical politics. So scholars who goes into thebureaucracy, practical time, thought and energy is spent on takingcare of practical and complex managerial problems that willgradually forget its main task as a religious expert. Involvement kiaiinto the realm of practical politics can be regarded as an accidentof history. Because such an impressive decision over a betrayal ofnature kiai. Kiai into the phenomenon of politicians as is nowhappening, it erodes the value of fresh charisma and blunt the kiaiin power and the public eye.